Clinical Outcomes of Total Ankle Arthroplasty With Total Talar Prosthesis. (August 2019) - Kanzaki, Noriyuki; Chinzei, Nobuaki; Yamamoto, Tetsuya; Yamashita, Takahiro; Ibaraki, Kazuyuki; Kuroda, Ryosuke
Background: Total ankle arthroplasty (TAA) has been developed to treat patients with end-stage ankle osteoarthritis (OA). However, there is often difficulty in treating complicated pathologies such as ankle OA with subtalar joint OA and severe talar collapse. Therefore, this study aimed to explore the short-term results and complications of TAA with total talar prosthesis, known as combined TAA, as the new techniques to treat such complicated pathology. Methods: We examined postoperative results including ankle range of motion, Japanese Society for Surgery of the Foot (JSSF) scale, and complications. There were 22 patients (15 women), with mean follow-up of 34.9 (range, 24–53 months), and the mean age was 72 (range, 62–80) years. The main indications for combined TAA included osteoarthritis (18 patients), rheumatoid arthritis (3 patients), and talar osteonecrosis with osteoarthritis (one patient). Results: The mean range of motion improved from 4.0 to 14.4 degrees in dorsiflexion and from 23.8 to 32.0 degrees in plantarflexion. The JSSF scale improved from 50.5 to 91.5 points. Prolonged wound healing occurred in 3 patients, and medial malleolus fracture occurred in 4 patients. Conclusion: Combined TAA was a reliable procedure for the treatment of not only ankle OA following avascular necrosis of talus but also of degeneration of both ankle and subtalar joints. Level of Evidence: Level IV, case series.